Teaching Moral Ethics through Sermons: A Case Study on Gregory of Nyssa - Jonathan Farrugia (Religions, 2023)
This article studies six sermons related to proper social behavior from a Christian perspective by fourth-century theologian Gregory of Nyssa. A brief comment on the dating and the context of the sermons is given before the different themes discussed in the different liturgical seasons are analyzed, and then the content of each of these sermons is explored in some depth. Following this, an analysis of the persuasive and instructive styles in these sermons is made, underlining the different ways the bishop exhorts his people according to the matters at hand. When discussing issues that set a bad example, such as the practice of usury and the rejection of correction, the language used is very harsh; in other cases, the tone is softer, such as when it comes to deciding whether one should postpone his baptism or not or how one should behave vis-à-vis the more needy in society; when dealing with sensitive issues like fornication, given the natural human weakness in this aspect, the language is much more pastoral. Finally, a comment on the narratives used concludes the study.